1998
DOI: 10.1200/jco.1998.16.5.1885
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic anemia after fludarabine therapy for chronic lymphocytic leukemia.

Abstract: HA associated with fludarabine therapy appears to be uncommon, but it can be severe and fatal, especially if a patient is re-treated with this drug after a previous episode of HA. The mechanism of this toxicity is unknown, but it may be caused by the release of a suppressed auto-antibody to a native red cell antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
2
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 6 publications
0
75
2
3
Order By: Relevance
“…Because T cell immunosuppression is a consequence, purine analogs could be successful in various autoimmune diseases, like rheumatoid arthritis, 4 even if autoimmune cytopenia, mostly hemolytic anemia, induced by fludarabine has been reported. 5 Our observation illustrates acquired hemophilia associated with CLL might be rapidly improved and cured with fludarabine and cyclophosphamide, without corticosteroids.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Because T cell immunosuppression is a consequence, purine analogs could be successful in various autoimmune diseases, like rheumatoid arthritis, 4 even if autoimmune cytopenia, mostly hemolytic anemia, induced by fludarabine has been reported. 5 Our observation illustrates acquired hemophilia associated with CLL might be rapidly improved and cured with fludarabine and cyclophosphamide, without corticosteroids.…”
Section: To the Editormentioning
confidence: 99%
“…[1][2][3][4] Recently, a chimeric M3:M2 case of acute promyelocytic leukemia was presented. 5 In November 1996, a 33-year-old Greek woman presented with anemia, thrombocytopenia and a white blood cell count of 28.0 × 10 9 /l with 60% blasts of typical M3 morphology. Her past medical Fludarabine is a new purine analogue with major activity in the treatment of CLL.…”
Section: To the Editormentioning
confidence: 99%
“…One major side effect of fludarabine in patients with CLL is autoimmune hemolysis 43,44 ; however, this phenomenon has not been described in larger studies involving patients with FL or MCL. This finding suggests that autoimmune hemolysis is not related exclusively to fludarabine use but might also depend on the subtype of lymphoproliferative disease being treated.…”
Section: Toxicitymentioning
confidence: 99%
“…The reported incidence of AIHA after fludarabine treatment varies from 11% to 21%. 21,22 It has been suggested that the profound lymphocytopenia following fludarabine therapy may result in T cell subset imbalance, which in turn may favor the emergence of autoreactive T cells.…”
Section: Figurementioning
confidence: 99%